Tratamiento de la emesis inducida por citotóxicos - Martín, Miguel; López, Sara (Psicooncología, 2004)
Nausea and vomiting are important side effects of most chemotherapy anticancer drugs, since nearly two thirds of the patients under chemotherapy have this toxicity in absence of antiemetic treatment. If uncontrolled, nausea and vomiting can severely impair the quality of life of patients. The present armamentarium of efficacious antiemetic drugs includes 5-HT3 receptor antagonist and corticosteroids. However, a certain percentage of patients under chemotherapy still experience nausea and vomiting in spite of the presently available antiemetics, so that new antiemetic drugs are needed.